1399. Efficacy of Daptomycin Combination with β-Lactams for Daptomycin-resistant Enterococcus faecium Harboring LiaSR Substitutions. (26th November 2018) - Kebriaei, Razieh; Rice, Seth; Singh, Kavindra; Stamper, Kyle; Dinh, An; Rios, Rafael; Diaz, Lorena; Murray, Barbara; Munita, Jose M; Tran, Truc T; Arias, Cesar; Rybak, Michael J
Abstract: Background: Daptomycin (DAP) is one of the mainstay treatments for Enterococcus faecium infections. However, development of resistance threatens its continued viability as a treatment option. Although the mechanisms of DAP resistance in enterococci are not fully comprehended, they are associated with alterations in cell envelope phospholipids assembly which leads to repulsion of the drug from cell exterior and diversion from the cell septum. Previous data suggest that combination of DAP with β-lactams has the potential to improve patient outcomes. In this investigation, we sought to evaluate combinations of DAP with ampicillin (AMP), ceftaroline (CPT), and ertapenem (ERT). Methods: E. faecium R497 harboring liaSFR mutations (DAP MIC of 16 mg/L) was evaluated in a simulated endocardial vegetation (SEV) pharmacokinetic and pharmacodynamic model over 336 hours at a starting inoculum of 10 9 log10 CFU/g of SEV. DAP alone at 10 mg/kg/day or DAP (6, 8, 10 mg/kg/day) in combination with AMP (2 g continuous infusion), CPT 600 mg q12h or ERT 1 g q24h were evaluated. The emergence of DAP resistance was determined daily over the course of the 14-day experiment. Results: DAP alone was not bactericidal and high-level DAP resistance was observed (MIC increase from 16 to 256 µg/mL) for all DAP alone regimens. Combination of DAP+AMP offered a significant reduction in log10 CFU/g amounts (up to 7 log10 CFU/g and to detection limits) in 24 hours in DAP10+AMP model with no further emergence of DAP resistance. Even in DAP 6 mg/kg/day with AMP (2 g), dramatic killing with no further emergence of resistance was observed. Neither CPT nor ERT in combination with DAP was effective against this strain. At higher doses of DAP (14 mg/kg/day) + CPT or ERT, a temporary (0–48 hours) CFU/g reduction was observed followed by regrowth and the further emergence of DAP resistance. Conclusion: Combination of DAP + AMP offered the most encouraging results against E. faecium R497. A DAP dose sparring effect was noted with DAP + AMP but not with CPT or ERT. The reason for the discrepancy is unknown and is under further investigation. Further evaluation of DAP plus β-lactam therapy is warranted to discover the most optimized DAP and β-lactam therapy to improve patient outcome and prevent the emergence of resistance. Disclosures: B. Murray, Paratek pharmaceuticals: Consultant and Scientific Advisor, Consulting fee and Speaker honorarium; Forest/Actavis: Grant Investigator, Grant recipient; Cubist/Merck: Grant Investigator, Grant recipient. C. Arias, Merck & Co., Inc.: Grant Investigator, Research support; MeMed: Grant Investigator, Research support; Allergan: Grant Investigator, Research support; M. J. Rybak, Allergan: Consultant, Grant Investigator and Speaker's Bureau, Research grant and Research support; Achaogen: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support; Bayer: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support; Melinta: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support; Merck: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support; Theravance: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support; Sunovian: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support; Zavante: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support; NIAID: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support